EVALUATION OF THE IMPLEMENTATION OF THE FREE NUTRITIOUS MEALS (MBG) POLICY IN REMOTE AREAS: ANALYSIS OF FOUR EDWARDS III VARIABLES IN THE 3T REGION OF NORTH KALIMANTAN - Piter; Zainal Fatah; Eny Haryati (International Journal of Multidisciplinary Reseach, 2026)
The Free Nutritious Meals (MBG) program is a large-scale affirmative policy, yet its national achievement has not been matched by effectiveness in underdeveloped, frontier, and outermost (3T) regions that face distinctive structural barriers. This study aims to evaluate MBG implementation in remote areas using Edwards III's theory, namely communication, resources, disposition, and bureaucratic structure, while identifying its main inhibiting factors. The population comprised all MBG-recipient schools and their implementers in North Kalimantan Province. The quantitative sample was determined by purposive sampling and comprised 60 respondents from 20 schools, while the qualitative stage involved 10 informants selected through snowball sampling. The study used a mixed-method approach with a sequential explanatory design. Quantitative data from a Likert questionnaire were analyzed descriptively, then deepened with qualitative data from interviews, observations, and documentation that were analyzed through data condensation, data display, and conclusion drawing, after which both results were integrated. The results show that implementation was in the moderate category (3.19 on a 1 to 5 scale). The disposition dimension obtained the highest score (3.74) and resources the lowest (2.69). The main barriers were technical and logistical, namely transportation, the cold chain, limited personnel, and supply continuity, while implementers' high commitment tended to mask systemic weaknesses. The study concludes that MBG effectiveness in remote areas is constrained not by implementers' will but by the system's capacity to overcome geographical barriers, so that Edwards III's four variables need to be complemented by a fifth dimension, namely the socio-cultural suitability of local food.